2017
DOI: 10.1155/2017/2862360
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Peer Victimization (Bullying) among Grades 7 and 8 Middle School Students in Kuwait

Abstract: Background. Peer victimization (bullying) is a universal phenomenon with detrimental effects. The aim of this study is to determine the prevalence and factors of bullying among grades 7 and 8 middle school students in Kuwait. Methods. The study is a cross-sectional study that includes a sample of 989 7th and 8th grade middle school students randomly selected from schools. The Revised Olweus Bully/Victim Questionnaire was used to measure different forms of bullying. After adjusting for confounding, logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
5
20
1
2
Order By: Relevance
“…The only research that found a relationship between the household composition and cyberbullying perpetration (Le et al 2017) also employed an instrument less commonly used in research (Le et al 2016). On the contrary, studies did find a relationship between the composition of the household and cybervictimization (Abdulsalam et al 2017;Bevilacqua et al 2017;Chen et al 2018;Garmy et al 2018) with instruments that have been extensively used in our study field (e.g., Olweus 1996) or items coming from research studies of recognized importance (e.g., Currie et al 2014;Genta et al 2009). Definitively, it could be concluded that the most reliable results point to a relationship between the household composition and cybervictimization.…”
Section: Contextual Family Variablesmentioning
confidence: 66%
See 3 more Smart Citations
“…The only research that found a relationship between the household composition and cyberbullying perpetration (Le et al 2017) also employed an instrument less commonly used in research (Le et al 2016). On the contrary, studies did find a relationship between the composition of the household and cybervictimization (Abdulsalam et al 2017;Bevilacqua et al 2017;Chen et al 2018;Garmy et al 2018) with instruments that have been extensively used in our study field (e.g., Olweus 1996) or items coming from research studies of recognized importance (e.g., Currie et al 2014;Genta et al 2009). Definitively, it could be concluded that the most reliable results point to a relationship between the household composition and cybervictimization.…”
Section: Contextual Family Variablesmentioning
confidence: 66%
“…Bevilacqua et al (2017) found that students from single-parent households were more likely to be cyberbullied. Abdulsalam et al (2017) found that children of divorced/widowed parents were more likely to be a cybervictim. Chen et al (2018) discovered that parents' divorce and separation were associated with cyberbullying victimization.…”
Section: Contextual Family Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on peer victimization in primary schools showed that boys are more likely to be peer victims than girls; however, relational victimization was most strongly associated with PTSD symptoms among girls, but not among boys [ 24 ]. Another study conducted in Kuwait revealed that boys are likely to be physical and relational victims [ 25 ]. By contrast, it has been known that girls are more at risk for emotional difficulties [ 26 ].…”
Section: Discussionmentioning
confidence: 99%